Grammaticalization and Language Change in Chinese - Xiu-Zhi Zoe Wu (Routledge Studies in Asian Linguistics, 2004)
This innovative study on the phenomenon of 'grammaticalization' and its manifestation in Chinese provides new insights into language change in Chinese and a large number of grammatical topics. Grammaticalization occurs in all of the world's languages. Xiu-Zhi Zoe Wu demonstrates general linguistic principles present and active in the phenomenon of grammaticalization whilst also describing the modelling of language in formal theoretical approaches to syntax; so this book fills two major gaps in the current study of linguistics. Grammaticalization and Language Change in Chinese illuminates how studies of language development and change provide special insights into the understanding of current, synchronic systems of language. Using patters from Chinese, the author establishes cross-linguistic generalizations about language change and grammaticalization. This book should be of great interest to Chinese linguists and readers interested in language change in different languages.